Filter quality factors of fibrous filters with different fiber diameter. Issue 2 (1st February 2021) - Kim, Han Bin; Lee, Woo Jin; Choi, Seuk Cheun; Lee, Ki Bong; Lee, Myong-Hwa
Abstract: Fibrous filters are effective for the removal of ultrafine particles and have been widely used. According to filtration theory, diffusion and interception are the main particle collection mechanisms for removing ultrafine particles, and these are greatly affected by fiber diameter. Particle collection efficiency by diffusion and interception increases as the fiber diameter decreases. Most of the previous studies conducted by researchers have focused on the effect of fiber diameter on filtration performance; however, they used filter media with different physical properties. Therefore, it is important to clearly understand the influence of fiber diameter alone on filtration performance in filters with the same physical properties (e.g., packing density, filter thickness, and fiber weight per unit area). In this study, PVA nanofiber filters with different fiber diameters (100, 201, and 306 nm) were prepared with other physical properties the same, using electrospinning. In addition, the effect of fiber diameter on filtration performance was examined by experimental and theoretical investigation. Filtration performance as determined by pressure drop and particle collection efficiency, increased with decreasing fiber diameter, as expected according to filtration theory. Furthermore, the filter quality factor (representing filtration performance), increased with decreasing fiber diameter. Copyright © 2020 American Association for Aerosol Research